2004
DOI: 10.1016/j.physd.2003.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of solitons of the multidimensional nonlinear Schrödinger equation: matter-wave breathers

Abstract: We demonstrate that stabilization of solitons of the multidimensional Schrödinger equation with a cubic nonlinearity may be achieved by a suitable periodic control of the nonlinear term. The effect of this control is to stabilize the unstable solitary waves which belong to the frontier between expanding and collapsing solutions and to provide an oscillating solitonic structure, some sort of breather-type solution. We obtain precise conditions on the control parameters to achieve the stabilization and compare o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(132 citation statements)
references
References 43 publications
(91 reference statements)
5
127
0
Order By: Relevance
“…[9] is most possibly the reason for the negative result obtained there. More recently, Montesinos et al [10] have also confirmed the conclusion of Ref. [9] that no stable three-dimensional soliton could be obtained by a variation of Kerr nonlinearity.…”
Section: Numerical Calculationmentioning
confidence: 62%
See 1 more Smart Citation
“…[9] is most possibly the reason for the negative result obtained there. More recently, Montesinos et al [10] have also confirmed the conclusion of Ref. [9] that no stable three-dimensional soliton could be obtained by a variation of Kerr nonlinearity.…”
Section: Numerical Calculationmentioning
confidence: 62%
“…The stabilization of such BEC solitons in two [9,10,13] and three [15] dimensions is already under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in the absence of a tight transversal trapping, higher dimensional extensions of 1D solitons are generally unstable [12]. However, by restricting the transverse direction(s) of the condensate, it is possible to obtain higher † † This technique was suggested in earlier works in various important applications, as e.g., a means to prevent collapse of higher-dimensional attractive BECs [193,203,410], to produce periodic waves [107], robust matter-wave breathers [241,242,411,412], and so on. dimensional soliton solutions that are stabilized for times longer than the lifespan of the experiments [414][415][416].…”
Section: Multidimensional Solitons and Collapsementioning
confidence: 99%
“…Spatial and temporal periodic changes of the scattering lengths have been shown to be effective tools to change stability properties of nonlinear excitations, leading to the existence of two dimensional bright solitons in one and two component attractive condensates [9][10][11][12][13]. Moreover, they were used to induce long lived Bloch oscillations [14][15][16], dynamical localization [17], Rabi oscillations [18] of BEC gap solitons in optical lattices, Faraday waves [19,20] etc.…”
Section: Introductionmentioning
confidence: 99%